1996
DOI: 10.1073/pnas.93.22.12593
|View full text |Cite
|
Sign up to set email alerts
|

A genetic selection for Caenorhabditis elegans synaptic transmission mutants.

Abstract: We have isolated 165 Caenorhabditis elegans mutants, representing 21 Synaptic transmission is a major mechanism for intercellular communication in the nervous system. Many of the events that mediate synaptic transmission occur presynaptically and center on the synaptic vesicle cycle. The major steps of the synaptic vesicle cycle were described 20-40 years ago by investigators using electrophysiology and electron microscopy (reviewed in refs. 1-3). In brief, neurons produce specialized vesicles that are transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
406
1
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(420 citation statements)
references
References 50 publications
9
406
1
4
Order By: Relevance
“…Aldicarb resistance can be quantified in a variety of ways, including acute assays, in which hypercontraction or paralysis are monitored over time (Lackner et al 1999;Nurrish et al 1999), or chronic assays, in which the ability to grow and reproduce is monitored (Miller et al 1996). We found that cho-1 mutants are just as sensitive as wild-type animals to 2 mm aldicarb in an acute assay (see below).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Aldicarb resistance can be quantified in a variety of ways, including acute assays, in which hypercontraction or paralysis are monitored over time (Lackner et al 1999;Nurrish et al 1999), or chronic assays, in which the ability to grow and reproduce is monitored (Miller et al 1996). We found that cho-1 mutants are just as sensitive as wild-type animals to 2 mm aldicarb in an acute assay (see below).…”
Section: Resultsmentioning
confidence: 72%
“…Resistance to the AChE inhibitor aldicarb is usually associated with decreased ACh release (Miller et al 1996). Aldicarb resistance can be quantified in a variety of ways, including acute assays, in which hypercontraction or paralysis are monitored over time (Lackner et al 1999;Nurrish et al 1999), or chronic assays, in which the ability to grow and reproduce is monitored (Miller et al 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis, we used a well-established pharmacological assay to analyze the changes in cholinergic signaling (Miller et al, 1996). In this assay, animals are exposed to the cholinesterase inhibitor aldicarb, and a time course of paralysis is used to quantify defects in synaptic function.…”
Section: Rab-3 and Rab-27 Control Synaptic Transmissionmentioning
confidence: 99%
“…Swimming (thrashing), pharyngeal pumping, and defecation were all measured on young adult hermaphrodites raised at 20°C as described previously (Miller et al, 1996). Acute aldicarb assays were performed as described previously (Lackner et al, 1999;Nurrish et al, 1999) using 2 mM aldicarb.…”
Section: Behavioral Assaysmentioning
confidence: 99%